Combined Surgical Techniques for the Management of Malignant Glaucoma - Jinfei Tang; Ergang Du; Xingyu Li (Journal of Ophthalmology)
Purpose. To characterize new combined surgical techniques for the management of malignant glaucoma. Methods. In a retrospective, interventional case series, goniosynechialysis, peripheral iridectomy, zonulo-hyaloidectomy, and anterior vitrectomy, with or without peripheral capsulectomy, were performed on nine eyes. If the patient was phakic, we performed both phacoemulsification and intraocular lens implantation. Results. Resolution of malignant glaucoma was achieved in all cases with anterior chamber deepening. Topical antiglaucoma medications were used to control the intraocular pressure in one eye. No recurrence was observed after a median follow-up of 9 months. No complications occurred during surgery or the postoperative period. Conclusions. The combined surgical methods can completely eliminate blockade and aqueous misdirection and represent a promising treatment for malignant glaucoma.